Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.2 - Negative Exponents and Scientific Notation - Exercise Set: 57

Answer

$\dfrac{7ab^{-4}}{7^{-1}a^{-3}b^{2}}=\dfrac{49a^{4}}{b^{6}}$

Work Step by Step

$\dfrac{7ab^{-4}}{7^{-1}a^{-3}b^{2}}$ Evaluate the division: $\dfrac{7ab^{-4}}{7^{-1}a^{-3}b^{2}}=7^{1-(-1)}a^{1-(-3)}b^{-4-2}=7^{2}a^{4}b^{-6}=...$ Simplify: $...=49a^{4}b^{-6}=\dfrac{49a^{4}}{b^{6}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.